A new attempt of applying hybrid team‐based and case‐based learning approach in dental materials science: Does it work? - Lin, Galvin Sim Siang; Tan, Wen Wu; Foong, Chan Choong (European journal of dental education, 2023)
Limited studies have been conducted on the use of a hybrid team-based learning (TBL) and case-based learning (CBL) approach in dental education. The present study aims to evaluate students' experience of the hybrid TBL-CBL in learning dental materials science subjects. All second-year undergraduate Bachelor of Dental Surgery (BDS) students were invited to participate in a TBL-CBL session. These participants were randomly allocated to six different groups of 10-12 students, and the session was conducted by one lecturer as the facilitator. A 23-item questionnaire assessing four domains (perceptions of effectiveness, teacher, team interaction and learning environment) was administered at the end of the TBL-CBL session. The response rate was 91.9% (n = 68). Mean scores for the questionnaire items ranged from 4.13 to 4.60 suggesting a positive perception among the students towards the hybrid TBL-CBL approach. Regarding the open-response questions, students emphasised that the TBL-CBL session was effective for team interaction and group discussions. However, students wished to have a better venue for future sessions. Positive perceptions of the students encourage future educators to consider the use of TBL-CBL approach in teaching dental materials science and to avoid the reliance on standalone conventional lectures. Future research could consider examining its effects on students' academic achievement as well as the perspectives of teachers regarding its adoption in different dental specialities.